Orbital shaking conditions augment human nasoseptal cartilage formation in 3D culture - Jovic, Thomas Harry; Zhao, Feihu; Jia, Henry; Doak, Shareen Heather; Whitaker, Iain Stuart (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: This study aimed to determine whether a dynamic orbital shaking culture system could enhance the cartilage production and viability of bioengineered nasoseptal cartilage.Methods: Human nasal chondrocytes were seeded onto nanocellulose-alginate biomaterials and cultured in static or dynamic conditions for 14 days. Quantitative polymerase chain reaction for chondrogenic gene expression (type 2 collagen, aggrecan and SOX9) was performed, demonstrating a transient rise in SOX9 expression at 1 and 7 days of culture, followed by a rise at 7 and 14 days in Aggrecan (184.5-fold increase, p<0.0001) and Type 2 Collagen (226.3-fold increase, p=0.049) expression. Samples were analysed histologically for glycosaminoglycan content using Alcian blue staining and demonstrated increased matrix formation in dynamic culture.Results: Superior cell viability was identified in the dynamic conditions through live-dead and alamarBlue assays. Computational analysis was used to determine the shear stress experienced by cells in the biomaterial in the dynamic conditions and found that the mechanical stimulation exerted was minimal (fluid shear stress <0.02 mPa, fluid pressure <48 Pa). Conclusions: We conclude that the use of an orbital shaking system exerts biologically relevant effects on bioengineered nasoseptal cartilage independently of the expected thresholds of mechanical stimulation, with implications for optimising future cartilage tissue engineering efforts.